Population genetic analysis of "Ensis directus" unveils high genetic variation in the introduced range and reveals a new species from the NW Atlantic - Vierna Fernández, Joaquín; Jensen, K. Thomas; González-Tizón, Ana M.; Martínez-Lage, Andrés (Marine Biology, 2012)
[Abstract] We report current genetic variation of populations of the razor shell Ensis directus (Conrad 1843) (Mollusca: Bivalvia: Pharidae) in native (North American) and introduced (European) ranges using nuclear and mitochondrial sequence-based markers. We expected less variation within the introduced range, especially considering the frequent mass mortality events observed in Europe since the species was recorded for the first time in 1978. However, we found higher variation in Europe. The possible significance of temporal fluctuations of genetic variation, limited effect of random genetic drift, and multiple introductions are discussed. Interestingly, the multiple-introduction hypothesis contrasts with the gradual colonisation of European coastal waters but is supported by trained clustering analysis and by the intensity of transatlantic shipping. Genetic and morphometric evidence strongly supports that examined individuals from a supposed E. directus population from Newfoundland (Canada) belong to a separate species. This new Ensis is formally described here and named E. terranovensis n.sp.